Gestão de estoques: uma proposta de reposição contínua para material médico hospitalar e medicamentos em um hospital universitário federal do estado do Rio Grande do Norte - Almeida Filho, João Carlos do Nascimento (2013)
The inventory management in hospitals is of paramount importance, since the supply materials and drugs interruption can cause irreparable damage to human lives while excess inventories involves immobilization of capital. Hospitals should use techniques of inventory management to perform replenishment in shorter and shorter intervals, in order to reduce inventories and fixed assets and meet citizens requirements properly. The inventory management can be an even bigger problem for public hospitals, which have restrictions on the use of resources and decisionmaking structure more bureaucratized. Currently the University Hospital Onofre Lopes (HUOL) uses a periodic replacement policy for hospital medical supplies and medicines, which involves one moment surplus stock replenishment, the next out of stock items. This study aims to propose a system for continuous replenishment through order point for inventory of medical supplies and medicines to the hospital HUOL. Therefore, a literature review of Federal University Hospitals Management, Logistics, Inventory Management and Replenishment System in Hospitals was performed, emphasizing the demand forecast, classification or ABC curve and order point system. And also, policies of inventory management and the current proposal were described, dealing with profile of the mentioned institution, the current policy of inventory management and simulation for continuous replenishment order point. For the simulation, the sample consisted of 102 and 44 items of medical and hospital drugs, respectively, selected using the ABC classification of inventory, prioritizing items of Class A, which contains the most relevant items in added value, representing 80 % of the financial value in 2012 fiscal year. Considering that it is a public organization, subject to the laws, we performed two simulations: the first, following the signs for inventory management of Instruction No. 205 (IN 205 ), from Secretary of Public Administration of the Presidency ( SEDAP / PR ), and the second, based on the literature specializing in inventory management hospital. The results of two simulations were compared to the current policy of replenishment system. Among these results are: an indication that the system for continuous replenishment reorder point based on IN 205 provides lower levels of safety stock and maximum stock, enables a 17% reduction in the amount spent for the full replenishment of inventories, in other words, decreasing capital assets, as well as reduction in stock quantity, also the simulation made from the literature has indicated parameters that prevent the application of this technique to all items of the sample. Hence, a change in inventory management of HUOL, with the application of the continuous replenishment according to IN 205, provides a significant reduction in acquisition costs of medical and hospital medicine